Optimization of operating conditions of the Fischer–Tropsch synthesis based on multi-objective differential evolution algorithm - Leite, Vinícius Reisdorfer; Fontana, Éliton; Mariani, Viviana Cocco (Journal of the Brazilian Society of Mechanical Sciences and Engineering, 2022)
A study on the Fischer–Tropsch synthesis was investigated employing a one-dimensional non-isothermal model in a fixed-bed reactor over a Co/Al 2 O 3 catalyst. The reaction kinetic follows a semi-empirical approach. Under multiple operating conditions and compared to experimental results, the presented model appropriately describes the product distribution. Afterward, optimizations using single- and multi-objective differential evolution (DE) algorithms were conducted. The minimum CH 4 selectivity and maximum CO conversion were obtained, through the single-objective DE optimization. The results indicate that the improvement of one objective is only reached by making reductions to the other objective, i.e., a trade-off between objectives. The optimal operating conditions employing the multi-objective algorithm found GHSV = 4002.17 Nml g cat - 1 h - 1 , H 2 / CO = 2.7, T = 501.63 K, P = 22.7 bar, and no inert content (%N 2 = 0). Conditions that yielded optimized CO conversion and CH 4 selectivity, respectively, of 60.21 and 6.65%.